Forecasting the real output using fractionally integrated techniques - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
The annual structure of the real GDP in the UK, France, Germany and Italy is examined in this article by means of fractionally integrated techniques. Using a version of a testing procedure due to Robinson (1994), we show that the series can be specified in terms of I(d) statistical models with d higher than 1. Thus, the series are nonstationary and non-mean-reverting. The forecasting properties of the selected models for each country are also examined at the end of the article.
urn:nbn:de:kobv:11-10049553
Keywords: C22; 330; Long memory; Fractional integration; Nonstationarity